2011
DOI: 10.1074/mcp.m110.000117
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteome Analysis Reveals Regulatory Sites in Major Pathways of Cardiac Mitochondria

Abstract: Mitochondrial functions are dynamically regulated in the heart. In particular, protein phosphorylation has been shown to be a key mechanism modulating mitochondrial function in diverse cardiovascular phenotypes. However, site-specific phosphorylation information remains scarce for this organ. Accordingly, we performed a comprehensive characterization of murine cardiac mitochondrial phosphoproteome in the context of mitochondrial functional pathways. A platform using the complementary fragmentation technologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
103
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 53 publications
0
103
0
Order By: Relevance
“…The authors suggested that the two phosphorylation sites (RKLGpSDVFpSQNV) may be in the context of MK2 or casein kinase I substrate motifs (50). Based on these results, we constructed a S511A/S515A double mutant form of M1 GFP-iPLA 2 ␥ and tested its activity in COS-1 cells.…”
Section: Mutations In Putative Erk Phosphorylation Sites Do Notmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that the two phosphorylation sites (RKLGpSDVFpSQNV) may be in the context of MK2 or casein kinase I substrate motifs (50). Based on these results, we constructed a S511A/S515A double mutant form of M1 GFP-iPLA 2 ␥ and tested its activity in COS-1 cells.…”
Section: Mutations In Putative Erk Phosphorylation Sites Do Notmentioning
confidence: 99%
“…The Ser-511 and Ser-515 phosphorylation sites were proposed to be a phosphorylation motif for MK2 (50), and given that complement was shown to activate MK2 via the ERK or p38 pathway (51), it was reasonable to examine if MK2 may be the kinase downstream of ERK that phosphorylates iPLA 2 ␥. However, we were not able to show stimulation of iPLA 2 ␥ after MK2 overexpression.…”
mentioning
confidence: 99%
“…This type of mechanism, whereby epigenetic modifications of the nuclear and mitochondrial genomes establish cell-specific programs based on intracellular cues, may go a long way in explaining differences in specific mitochondrial features observed across fiber types. Tools capable of measuring genome-wide methylation profiles (13), proteomics (8,33), posttranslational modifications of mitochondrial proteins (26,78), and metabolomic profiling (113) may prove valuable in deciphering the origin of these mitochondrial phenotypic variations across cell types.…”
Section: C634mentioning
confidence: 99%
“…They are easy to install and manage and are well supported by bioinformatics institutes like the European Bioinformatics Institutes (EBI). EBI's Maven repository 10 contains packages for accessing and managing data about proteins (Patient et al, 2008), chemicals (Deng et al, 2011), molecular interactions (Aranda et al, 2011;Kerrien et al, 2012) Competing interests: the authors have declared that no competing interests exist.…”
Section: Postersmentioning
confidence: 99%